Role of magnetic resonance imaging in predicting the efficiency of cardiac resynchronization therapy in patients with left ventricular non-compaction and heart failure - E. A. Mershina; D. A. Filatova; R. P. Myasnikov; O. V. Kulikova; A. N. Meshkov; M. S. Kharlap; V. E. Sinitsyn (Российский кардиологический журнал, 2024)
Aim. To evaluate the role of magnetic resonance imaging (MRI) in predicting the efficacy of cardiac resynchronization therapy (CRT) in patients with left ventricular non-compaction (LVNC) and heart failure (HF).Material and methods. This observational retrospective study included 26 patients with a morphological signs of LVNC cardiomyopathy according to echocardiography (Chin, Jenni, Stollberger criteria) and MRI (Petersen criterion). All patients underwent CRT implantation. The changes of the left ventricular size and function were assessed using echocardiography. Before the CRT procedure, all patients underwent contrast-enhanced cardiac MRI.Results. According to a response to CRT, patients were divided into 3 following groups: responders (a decrease in left ventricular (LV) end-diastolic volume (EDV) according to echocardiography from 15 to 30%, a decrease in HF functional class), super-responders (a decrease in LV EDV by more than 30%) and non-responders (failure to meet the response criteria). The study identified factors influencing the CRT results, the most significant of which were the familial LVNC cardiomyopathy, sex and age of patients, as well as following parameters of cardiac morphology: myocardial fibrosis according to MRI, myocardial non-compaction severity, LV volume index.Conclusion. MRI is a technique that can make a significant contribution to predicting the CRT effectiveness in patients with LVNC and HF. Therefore, it should be performed in all patients before CRT to optimize the selection procedure and exclude patients who are unlikely to benefit from CRT.